Identifikasi dan Analisis Vegetasi Gulma Pada Tipe Agro-Ekosistem Sawah di Desa Mata Air, Kabupaten Kupang - Romi Fahri; Elesta Banamtuan; Yosni Kiuk; Stefany Darsan; Fany Juliarti Panjaitan; Mariano Trivandy Ngasu Nganggo (UNIVERSITAS LABUHANBATU, 2026)
The presence of weed vegetation is one of the main limiting factors in increasing the productivity of paddy fields in the semi-arid region of Kupang Regency. This study aims to identify the species composition and analyse the community structure of weeds in the paddy field agro-ecosystem in Mata Air Village using the Summed Dominance Ratio (SDR) parameter. The study was conducted using a quadrat method with 24 sample plots (0.25 m²) laid out randomly. Data were analysed quantitatively to determine Relative Density (RD), Relative Frequency (RF), and SDR. The results identified three main groups of weeds with varying levels of dominance. Sedges were the most dominant group with the highest SDR value (38.74%), driven by a very high individual density in the field (RD 47.85%). Grasses ranked second (SDR 31.64%), followed by broadleaves with an SDR value of 29.62%. Although they had the lowest dominance, broad-leaved weeds exhibited the most even spatial distribution across the study area (FR 38.89%). The combined dominance of sedges and grasses, which exceeded 70%, indicates that competition for nutrients and space at the study site is heavily influenced by monocotyledonous vegetation. These findings suggest the need for the integration of intensive soil management and appropriate water management as part of an Integrated Weed Management (IWM) strategy in Mata Air Village. Keywords: weeds, vegetation analysis, mata air village, paddy fields, SDR